Urinary Incontinence and Early Outcome after Acute Ischemic Stroke - Keilani, M.; Lalouschek, W.; Mittlböck, M.; Greisenegger, S.; Crevenna, R. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2014)
Purpose: To relate the occurrence of incontinence due to acute ischemic stroke (AIS) by demographic factors, concomitant diseases, and severity of stroke and to investigate the associations of incontinence due to stroke with early clinical outcome within the first week after event.Materials and Methods: Of 2 659 consecutive inpatients with AIS who were admitted within 72 h of symptom onset, patients with de novo incontinence after event (n=303, m:f=131:172, age:median=74a, min=25, max=95) were analyzed in comparison to continent patients (n=1 494, m:f=877:617, age:median=67a, min=18, max=93). The occurrence of incontinence due to stroke was measured by history taking and clinical examination. The occurrence of incontinence due to stroke was analyzed in relation to concomitant diseases, medical complications occurring within the 1st week after admission, the National Institute of Health Stroke Scale 24–36 h after admission (NIHSS), and the modified Rankin Scale at 5–7 days after admission (mRS).Results: In patients admitted due to acute stroke age (p<0.0001), NIHSS (p<0.0001), fever prior to stroke (p=0.0070), dementia prior to stroke (p=0.0246), and female sex (p=0.0391) were associated with incontinence. A stepwise logistic regression model identified NIHSS (p<0.0001), age (p=0.0052), incontinence (p=0.0076), female sex (p=0.0128), and prior stroke (p=0.0275) as significant risk factors for a mRS≥3. As compared to continent patients these patients were significantly more affected from complications like fever (8% vs. 1.5%, p<0.0001), pneumonia (7% vs. 0.7%, p<0.0001), heart failure (6% vs. 0.5%, p<0.0001), hemorrhagic transformation of ischemic stroke (4% vs. 0.3%, p<0.0001), and urinary tract infection (4% vs. 0.5%, p<0.0007).Conclusions: In comparison to continent patients, incontinent patients had a worse functional outcome, more early vascular complications, and infections. Higher age and stroke severity may be predisposing factors for poor functional outcome.
Keywords: acute ischemic stroke; urinary incontinence; early outcome; complications